A qualitative study exploring the impact and consequence of the medicines use review service on pharmacy support-staff - Latif A; Boardman HF; Pollock K (Centro de Investigaciones y Publicaciones Farmaceuticas, 2013)
Background: Pharmacy support-staff (pharmacy technicians, dispensers and Medicines Counter Assistants) support the delivery of pharmaceutical and retail functions of the pharmacy. Workflow is supervised and at times dependent upon the pharmacist's presence. Policy makers and pharmacy's representative bodies are seeking to extend the community pharmacist's role including requiring the pharmacist to undertake private consultations away from the dispensary and shop floor areas. However, support-staff voices are seldom heard and little is known about the impact such policies have on them.Objective: The objective of this study is to explore the impact and consequences of the English Medicine Use Review (MUR) service on pharmacy support-staff. Method: Ten weeks of ethnographic-oriented observations in two English community pharmacies and interviews with 5 pharmacists and 12 support-staff. A thematic approach was used to analyse the data.Results: Despite viewing MURs as a worthwhile activity, interviews with support-staff revealed that some felt frustrated when they were left to explain to patients why the pharmacist was not available when carrying out an MUR. Dependency on the pharmacist to complete professional and accuracy checks on prescriptions grieved dispensing staff because dispensing workflow was disrupted and they could not get their work done. Medicines Counter Assistants were observed to have less dependency when selling medicines but some still reported concerns over of customers and patients waiting for the pharmacist. A range of tacit and ad hoc strategies were consequently found to be deployed to handle situations when the pharmacist was absent performing an MUR. Conclusions: Consideration should be given to support-staff and pharmacists' existing work obligations when developing new pharmacy extended roles that require private consultations with patients. Understanding organisational culture and providing adequate resourcing for new services are needed to avoid improvisations or enactments by pharmacy support-staff and to allow successful innovation and policy implementation.